Model nanoparticles in catalysis - Vinod, C. P.; Vysakh, A. B.; Sreedhala, S. (Metal nanoparticles and clusters: advances in synthesis, properties and applications, 2017)
The importance of surface structure in catalysis is well documented by a large volume of surface science studies carried out on single crystal surfaces. Recent years has seen rapid strides in the synthesis of structured nanomaterials with varying morphologies and architecture. There is a growing interest in utilizing model nanoparticles like morphology-controlled nanostructures and core–shell-like bimetallic nanoparticles in catalysis. Apart from showing unprecedented reactivity, they serve as a model surfaces to answer many fundamental question in catalysis and also to arrive at structure vs activity correlations in heterogeneous catalysis. This chapter gives an introduction to such nanomaterials and recent advances in utilizing these materials for catalytic applications.